Spontaneous extrusion of the peritoneal catheter through the intact abdominal wall: report of two cases - Carlos Umberto Pereira; Gabriela Ferreira Kalkmann; Humberto Belém de Aquino (Brazilian Society for Pediatric Neurosurgery, 2021)
Introduction: Ventriculoperitoneal shunt (VPS) is a neurosurgical intervention widely used in the control and treatment of hydrocephalus. The migration of the peritoneal catheter through the abdominal wall is an uncommon complication and its pathophysiology is unknown. Patients and Methods: Two cases of the peritoneal catheter extrusion through the abdominal wall are reported in patients with congenital hydrocephalus. Results: Were discovered after removal of the bypass system and systemic antibiotic therapy, followed by replacement of new bypass, with excellent results. Conclusion: In the presence of this complication, surgical treatment is indicated, through complete removal of the system, systemic antibiotic therapy and subsequent replacement of a new system.